Two-tier local government governance in selected advanced countries: experiences and policy implications for Vietnam - Doan Thi My Hanh (Journal of State Management, 2025)
This study analyzes the two-tier local government models in France, Japan, Germany, and the United States to draw lessons for reforming the organization of state apparatus in Vietnam. Based on the theoretical foundations of local government organization, it clarifies the principles of decentralization, autonomy, accountability, and effective public governance. International experience highlights the importance oftransparent institutions, financial autonomy, competent personnel, and the application of technology in governance. In Vietnam, the two-tier model has been implemented since July 1, 2025, under Law No.72/2025/QH15, replacing the traditional three-tier structure. The article examines the challenges during the transition and proposes solutions to improve the legal framework, ensure substantive decentralization, enhance implementation capacity, reform public finance, strengthen oversight, and promote accountability - thereby contributing to building an effective, modern, and democratic local government.